Age-dependent flexion relaxation phenomenon in chronic low back pain patients - Zhang, Tianwei; Firouzabadi, Ali; Yang, Daishui; Liu, Sihai; Schmidt, Hendrik (Frontiers in Bioengineering and Biotechnology, 2024)
The flexion relaxation phenomenon (FRP) is characterized by suddenly reduced paraspinal muscle activity during full flexion. Previous studies showed significant differences in FRP and flexion angles in chronic low back pain (cLBP) patients compared to individuals without back pain (no-BP). However, the relationship between FRP and flexion angles remains insufficiently understood in older populations.Thus, this study investigated the relationship between FRP and flexion angles concerning to the age and presence of cLBP.: Forty no-BP subjects (20m/20f; mean age 41.5 years) and thirty-eight cLBP patients (19m/19f; mean age 43.52 years) performed maximum full upper body flexion task. Electromyographic (EMG) measurements were conducted to assess the activity of lumbar erector spinae (ESL), thoracic erector spinae (EST), and multifidus (MF).Lumbar, thoracic, and pelvic angles at the onset (OnsetL/T/P) and offset of the FRP (OffsetL/T/P) and maximum trunk inclination (MaxL/T/P) were calculated. The FRP was evaluated using a flexion relaxation ratio (FRR).Results: cLBP patients showed smaller FRR in MF and right ESL compared to no-BP individuals (p<0.05), while no differences were found in flexion angles between two groups. Subjects over 40 showed smaller FRR in MF and ESL, and smaller flexion angles on OffsetL and MaxL (p<0.05). Age-related analysis in the cLBP group revealed that patients over 40, compared to younger ones, had smaller FRR in MF and ESL, and smaller values in all thoracic and lumbar flexion angles (p<0.05). While in no-BP group, significant larger flexion angles in OnsetL and OffsetT (p<0.05) were observed in participants over 40. Pain-related analysis in the older group revealed that the cLBP patients, compared to no-BP individuals, had smaller FRR in right MF and right ESL, and smaller values in all lumbar and thoracic flexion angles (p<0.05), while in younger group, there were no significant pain-related differences in FRR, with larger values in all lumbar flexion angles (p<0.05).Our findings indicate a reduction or absence of FRP in cLBP patients compared to no-BP individuals, with age being a significant factor as those over 40 showed smaller FRP and flexion angles compared to younger individuals.